2022
DOI: 10.1039/d1sc06694c
|View full text |Cite
|
Sign up to set email alerts
|

Manganese(i)-catalyzed access to 1,2-bisphosphine ligands

Abstract: Chiral bisphosphine ligands are of key importance in transition-metal-catalyzed asymmetric synthesis of optically active products. However, the transition metals typically used are scarce and expensive noble metals, while the synthetic routes...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 66 publications
0
19
0
Order By: Relevance
“…The same group expanded the HP strategy toward α,β-unsaturated phosphine oxides to form a range of enantiopure 1,2-bisphosphine ligands. 77 2.3. Chemoselectivity.…”
Section: Stereoselectivity Product Distributions Due To Stereoselecti...mentioning
confidence: 99%
See 1 more Smart Citation
“…The same group expanded the HP strategy toward α,β-unsaturated phosphine oxides to form a range of enantiopure 1,2-bisphosphine ligands. 77 2.3. Chemoselectivity.…”
Section: Stereoselectivity Product Distributions Due To Stereoselecti...mentioning
confidence: 99%
“… Mechanistically, the authors suggested that the HP proceeded via metal–ligand cooperation, and the origin of the enantioselectivity was assessed by computational studies. The same group expanded the HP strategy toward α,β-unsaturated phosphine oxides to form a range of enantiopure 1,2-bisphosphine ligands …”
Section: Hydrophosphinationmentioning
confidence: 99%
“…Organophosphines are integral molecules in catalysis, synthetic chemistry, materials science, and more. Metal-catalyzed hydrophosphination, the addition of a P–H bond across an unsaturated substrate, is one of the most promising and atom-economical P–C bond-forming reactions. Progress has been made in expanding the available catalysts, scope, and selectivity of hydrophosphination in recent years. However, limitations remain that hamper the synthetic utility of hydrophosphination. , Among the most notable limitations with known catalysts is that they often require special preparation and/or complex ancillary ligands and that most precatalysts are not air- and water-stable (i.e., not convenient). Known catalysts also have limitations in reactivity, often stymied by unactivated or highly substituted substrates, especially in intermolecular reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…The same catalyst was also viable to hydrophophinate α,β-unsaturated phosphine oxides with good to excellent ee (Scheme 124b). 505 The TON in the latter case is slightly lower than the former. Several reducible functionalities and heterocycles were well-tolerated by the corresponding alkyl phosphines.…”
Section: Manganese-catalyzed Hydroelementation Reactionsmentioning
confidence: 86%